PENGARUH KUALITAS PELAYANAN DAN HARGA YANG DI MEDIASI OLEH KEPUASAN PELANGGAN SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN DI SWALAYAN SENA REBUNG BLANGKEJEREN - Surni Gayo; Sulaiman Sulaiman (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
the purpose of this study is to find out this study aims to examine the effect of service quality and prices mediated by customer satisfaction and its impact on customer loyalty to Sena Rebung Supermarket in Blangkejeren. The sampling method in this study used purposive sampling with a sample of 100 respondents. Statistical analysis using multiple linear regression by first using the normality test, multicollinearity test and heteroscedasticity test performed using SPSS version 16. Based on the collected data obtained by the average value of service quality variables of 4.35, the price variable is 4.39 , then the customer satisfaction variable is 4.28, and the customer loyalty variable of 4.35 can be concluded with good judgment. The data analysis technique used to process quantitative data using the t-test formula on a significant level α = 0.05. So, Ho (null hypothesis) is accepted and Ha (alternative hypothesis) is rejected. The results of this study indicate that Service Quality and Price variables mediated by customer satisfaction have a significant effect on customer loyalty. The author suggests the next researcher to do more in-depth research on the effect of service quality, prices mediated by customer satisfaction and their impact on customer loyalty for other research objects, namely by including other factors / variables not examined in this study that can affect these variables.Keywords: service quality, price, customer satisfaction, customer loyalty